2426-PUB: Circulating WBC, RBC, and Hemoglobin Level in Relation to Metabolic Syndrome and Incident Prediabetes in a Biracial Cohort of Normoglycemic Subjects with Parental Type 2 Diabetes - ABUTINEH, IMAN; UMEKWE, NKIRU A.; ARIGANJOYE, FOLABI; DAGOGO-JACK, SAMUEL (Diabetes (New York, N.Y.), 2019)
Objective: We assessed the relationships among blood cell counts, metabolic syndrome (MetS), and prediabetes risk in a biracial cohort of African Americans (AA) and European Americans (EA) with parental type 2 diabetes mellitus (T2DM). Methods: We studied 603 normoglycemic subjects (264 EA, 339 AA), mean (+SD) age 46.14 ± 10.58 y and BMI 31.1 + 7.30 kg/m2. Each subject underwent clinical examination and OGTT. Blood specimens were analyzed for RBC, WBC and differentials, and lipids. MetS markers were identified using NCEP cut-offs for waist, blood pressure, HDL cholesterol and triglyceride (TG) levels. Results: Total WBC count correlated positively with waist circumference (P=<0.001), TG (P=0.018) and fasting plasma glucose (FPG) (P=0.023) and inversely with HDL level (P=0.005), as did segmented neutrophil and monocyte counts. RBC count also correlated positively with waist (P= 0.0002), TG (P= 0.0004), FPG (P=0.035) and WBC count (P=0.0016) and inversely with HDL cholesterol level (P=<0.0001). Hemoglobin (Hb) and hematocrit (Hct), both strongly reflecting RBC count (r=0.75, P=0.0001), mirrored the association with MetS markers seen with RBC. Among 372 subjects followed longitudinally for 5 y, baseline MetS markers, absolute eosinophil and basophil counts, and Hb significantly predicted progression to prediabetes. After adjustment for age and BMI, logistic regression odds ratio [95% CI] for incident prediabetes was 1.37[1.094-1.633], P=0.0045 for MetS; 1.21[1.037-1.405], P=0.015 for Hb; 1.006[1.002-1.011], P=0.0093 for absolute basophil count; and 1.003[1.000-1.005], P=0.0237 for absolute eosinophil count. Conclusions: The known association between cardiometabolic risk and WBC extends to RBC count as well. Moreover, Hb level, eosinophil and basophil counts specifically predict increased risk of prediabetes, probably via proinflammatory and iron-related mechanisms.